Preparation, characterization, and application of camellianin A/soy protein isolate covalent complexes - Gao, Peng; Nie, Yuanyang; Zhou, Yingxuan; Ge, Wupeng (Frontiers in Nutrition, 2025)
Alkaline-assisted processing facilitated the development of camellianin A (CA)-soy protein isolate (SPI) conjugates, with systematic characterization of polyphenol incorporation effects on macromolecular architecture and emulsion stabilization capacity. Multi-spectroscopic profiling confirmed CA-induced structural reorganization of SPI matrices, verifying conjugate formation. Dose-dependent enhancement patterns were observed, where increased CA loading positively correlated with total phenolic content, surface hydrophilicity, ABTS radical scavenging activity and reducing power. The derived nanoemulsions demonstrated superior oxidative stabilization capacity and storage stability, outperforming SPI-only stabilized systems. Our results can advance the utilization of CA in functional foods, providing practical guidance for developing novel food-grade nanoemulsions with enhanced delivery efficacy.